STATELESS PERSON DAN KEJAHATAN PERANG DI PALESTINA PERSPEKTIF HUKUM HUKUM HUMANITER INTERNASIONAL - Asa Barno Happy Ramadhany; Indriyana Dwi Mustikarini; Sarah Deghmoum (Journal of Indonesian Comparative of Syari'ah Law, 2025)
The purpose of this study is to analyze the status and protection of stateless persons affected by prolonged war. Stateless persons in Palestine are at high risk due to armed conflict, especially since they are not protected by any country and no one guarantees their human rights. This study uses a normative legal methodology by examining library materials to explore why and how the status and protection of stateless persons in Palestine is determined. This method is useful for identifying legal rules, principles, and doctrines to address the legal issues in this study. The results of the study show that there is a huge normative and practical gap. Although international humanitarian law provides a very solid framework, its effectiveness is limited due to Israel's non-compliance with international law. This reflects the imbalance between legal norms and the reality of enforcement and implementation, as well as the need to draft and ratify a Citizenship Law for all stateless persons in the world that is internationally recognized to strengthen the protection of international stateless persons in future armed conflicts, then amend the protocol on stateless persons in the 1949 Geneva Convention, and increase the active role of ICC State Parties, UNHCR and ICRC in fighting for the protection of stateless persons in conflict zones.